Growing Up with Expectations. Better Understanding the Expectations of Community Partners in Participatory Action Research Projects - Ragan, Doug; Wilkinson, Clarissa (Les ateliers de l'éthique / The Ethics Forum, 2009)
This paper challenges the assumption that youth and youth agencies are in a condition of equality when entering a participatory action research (PAR). By asserting that it is not a state of equality that practitioners nor youth should assume nor be immediately striving for, but a consistently equitable process, this article draws from and reflects on the relationship between young people and researchers who have used a PAR methodology in action oriented projects. Using the UNESCO Growing up in Cities Canada project as a case example, this review extrapolates from and reflects on challenges faced by the project as a whole. Using semi-structured interviews to explore the roles of adults and youth, a number of strategies are highlighted as the techniques used to overcome these challenges. The discussion concludes with further reflection on the complexities of equality and equity, recommending a number of actions that have the potential to create an equitable environment in PAR projects similar to the one examined.